The Impact of Pedophilia: Crisis on the Universal Church - Scicluna, Charles J. (Iustitia, 2011)
The author presents the issue of pedophilia affecting the Universal Church under four main headings highlighting various aspects related to them: 1. Sexual Abuse of Minors by Clerics is a Grave Violation of Divine Positive and Ecclesiastical Law, 2. Sexual Abuse of Minors by Clerics is a Tragic Wound to the Church, 3. Truth as the Basis of Justice: Justice is at Times Called Truth; Justice as A Participation in the Truth Evokes A Response from the Individual's Conscience; Respect of the Truth Generates Confidence in the Rule of Law; Disrespect for the Truth Generates Distrust and Suspicion; The Protection of Rights is Implemented within the Context of the Concern for the Common Good; Respect for Procedural Laws Avoids Unfortunate Distortions of the "Pastoral" Nature of Church Law, and finally 4. The Role of the Catholic Church in the Prevention of Sexual Abuse of Minors: The Well-being of the Child as a Paramount Concern; The Care and Respect of the "Innocence" of the Child; The Protection of the Right to a Healthy Upbringing; Awareness of Child Abuse as a Tragic Wound; Empowerment of Children and Communities; Education; Disclosure; Formation and Screening of Pastoral Agents; Codes of Conduct; Cooperation with State Agencies; Care for Victims and Perpetrators; Welfare Principle in Decisions Concerning Personnel; Openness to Research and Development; Commitment and Accountability.